Recent Population and Nesting Trends of the Endangered Vulture Gyps Species in India - Dr. Gargi (International Journal of Engineering and Management Research, 2021)
The information on population variation between the seven species of vultures in Rajasthan's Thar Desert is extremely important. In the Thar Desert of Rajasthan, a systematic study was conducted with the goal of obtaining data on the demography, breeding, and nesting records of vulture species beginning in 2016 and continuing for three consecutive years. The population of resident and migratory vulture species was trended using linear regression. White-backed vultures had the lowest population trends, whereas Egyptian vultures showed the highest. Potential records of resident vulture species nesting were also appropriately acquired. Even after Diclofenac was banned in 2006, patterns of decreases, the presence of dead birds, different unintentional tragedies, habitat degradation, and windmills point to some potential causes.